Upaya Meningkatkan Pengembangan Lembar Kerja Siswa IPA Terpadu Berbasis Pemanfaatan Laboratorium pada Tema Ciri-Ciri Makhluk Hidup di Kelas VII A SMP Negeri 24 Kota Jambi - Resti Pinna St. Rumahorbo (Jurnal Ilmiah Dikdaya, 2019)
the IPA is a science that studies the concepts, processes, and the fact that there is in nature. IPA occupy an important role in education. IPA directly related to existing problems in the daily life of the life process, interactions with the environment and the activities that occur in life. Things aspects influenced researchers to develop the student's Worksheet IPA based integrated utilization of laboratory that is not yet the availability of learning materials, a lack of utilization of Integrated Science laboratories as well as the condition of the students who are less active in follow the process of learning the integrated IPA. This research aims to know the feasibility of utilization-based integrated Science laboratory and to find out if the Student Worksheets can enhance student learning outcomes. The research method used is Research and Development. At this stage of validation by the validator component that includes content, language and presentation earned an average score of 97.56% shows the worksheet this very worthy Students in learning. It supported the response of teachers who achieve 98.33% and 91% of the student's response States that the student Worksheet is very interesting and may encourage students to be more active in learning. This Student worksheets can enhance cognitive learning results students achieve 0.71 which is a high increase in criteria. From the analysis it was concluded that IPA Students Worksheets based integrated utilization of laboratory is well worth the use in the learning process and can improve student learning outcomes.